Wilson’s Disease: Diagnosis of Wilson’s Disease in Ethiopian Young Sisters - Nebiyu Bekele; Frew Ewnetu; Tigest Hailu; Zerubabel Tegegne; Abilo Tadesse (Case Reports in Medicine)
Background. Wilson’s disease is an inherited autosomal recessive disorder of copper metabolism. Clinical signs, biochemical parameters, histologic findings, and/or ATP7B genetic testing are required to diagnose Wilson’s disease. Case Presentation. 25-year-old and 22-year-old young women (siblings) presented to the University of Gondar Hospital, Northwest Ethiopia, with difficulty of keeping balance of 3-year duration and progressive extremity weakness of 5-year duration, respectively. Both siblings had visible ocular Kayser–Fleischer rings, low serum ceruloplasmin level and increased urinary copper content, ultrasound-evidenced cirrhotic liver disease, and axial T2-weighted MRI hyperintensities in basal ganglia, thalamus, and brainstem (midbrain and pons). Diagnosis of Wilson’s disease was established in both patients using a diagnostic scoring system proposed by “8th International Meeting on Wilson Disease and Menkes Disease, Leipzig (2001).” Treatment with D-penicillamine as a chelator and zinc sulphate as a metalothionein-inductor was started. Screening of their family members was recommended. Conclusion. Wilson’s disease, declared to be an orphan disease, requires clinical acumen of physicians and expensive investigation modalities for prompt recognition and is inaccessible as required, lifelong drugs for treatment.